Website Penetration Testing With SQL Injection Technique Using SQLMAP on Termux - Gilang Ryan Fernandes; Ika Mei Lina (Politeknik Piksi Ganesha Indonesia, 2024)
Websites make it easier for us to find information or do our daily work. Almost all companies have websites, be it company profiles or application websites. With the development of technology, some programmers forget about website security. Websites with security weaknesses can be easily hacked, such as changing appearance to taking essential data. One thing to watch out for is external factors in the form of attacks carried out by hackers using the SQL Injection technique. This technique can find and take all databases stored on the website server. The purpose of this study is so that programmers and companies, in general, can be more careful with this attack so as not to experience losses from both the company and the consumer side. The results obtained in this study show that SQL injection attacks can cause significant losses because they can modify and take over the database on the attacked website. This tool also runs automatically so that laypeople without an understanding of hacking can carry out this attack. Thus, programmers can secure their websites using techniques to secure SQL Injection attacks.